Efficiency of the body of public managers and the modernization of the state - Benites Paniagua, Lisberth Kevelin (2022)
The current study “The efficiency of the body of public managers and the modernization of the state” had as a general objective to determine the relationship between the efficiency of the body of public managers and the modernization of the state in the National Center for Risk Assessment, Prevention and Reduction of Disasters-CENEPRED, year 2019. This work is carried out quantitatively. Methods: Under the non-experimental cross-sectional design and the level of causal correlation, the total is made up of 60 CENEPRED collaborators, for convenience a sample was selected, using surveys as data collection techniques and questionnaires as tools. The result is a correlation coefficient of 0.885, so it is inferred that there is a highly positive internal correlation between the variables studied. However, a bilateral significance of less than 0.05 was obtained, so the null hypothesis was rejected and the alternative hypothesis was accepted. The conclusion reached is that there is a significant relationship between theefficiency of the body of public managers and the modernization of thestate in the National Center for Evaluation, Prevention and Disaster Risk Reduction-CENEPRED, 2019.